Історичний аналіз залізорудної промисловості Житомирщини - Нонік, Л.Ю. (Питання історії науки і техніки, 2007)
Рассмотрены предпосылки развития железорудной промышленности на Житомирщине на протяжении XVI–XIX ст. Исследовано развитие первых доменных заводов Полесья, показан их вклад в становление металлургической базы бывшей Российской империи. The pre-conditions of development of iron-ore industry on Zhitomir region during the XVI-XIX century is defined. Development of the first blast-furnace factories of Polissya is explored, their contribution to becoming of metallurgical base of the former Russian empire is shown.